Electrolyte concentration and nafion membrane effects on supercapacitor discharge dynamics and charge retention - Jagendra Chaudhari; Sangita Rai (Journal of Physics: Theories and Applications, 2026)
Supercapacitors (SCs) are promising energy storage devices due to their high charge retention and rapid discharge capabilities. However, the efficiency of supercapacitors can be influenced by factors such as the choice of separator material and electrolyte concentration. This study investigates the performance of SCs fabricated using Nafion separators with Na₂SO₄ electrolytes of varying concentrations (1M and 0.5M) and charging conditions. The objective of this research is to evaluate the self-discharge behavior, capacitance, and voltage stability of supercapacitors to determine the optimal configuration for high-performance energy storage. The methodology involves fabricating SCs with Nafion separators and charging them under different voltages (1V, 1.2V, 1.4V) for varying time intervals (1 minute, 1.5 minutes, and 2 minutes). Self-discharge characteristics were monitored, and capacitance was calculated using the capacitor discharge equation. The experiments also included discharge tests using a 500-ohm resistor to simulate realistic usage. Major findings include that SCs with Nafion separators and 0.5M Na₂SO₄ electrolyte exhibit significantly lower self-discharge rates and more stable voltage profiles than those with napkin paper separators. Higher charging voltages and longer charging times lead to better charge retention. These results suggest that Nafion membranes and optimized electrolyte concentrations enhance supercapacitor performance, making them suitable for long-term, efficient energy storage applications.